Transaksi Emoney terhadap Layanan Gopay pada Aplikasi GoJek Perspektif Ekonomi Syariah - Sukma Indra; Zuliana Rofiqoh (Al Ahkam, 2019)
Advances in science and technology can have many effects on changes in people's behavior and habits. This makes people need something that is fast, easy and simple to support their every activity, as well as in terms of payment. A safer, faster and more efficient payment system is found in the Go-Pay service provided by Go-Jek. Payment system through Go-Pay is a solution that is needed by the community. However, there is something rather strange when viewed from the perspective of Islamic economics. By using a normative approach and qualitative data analysis, the results in this study conclude that payments using the Go-Pay balance in the Go-Jek application can be used by Muslim communities with the note that Go-Pay must be in accordance with the principles of shari'ah that are avoided from ribawi, gharar, maysir, tadlis, risywah, israf, and transactions on illicit or immoral objects. In addition, the existence of Go-Pay is included in the protection of assets (hifdz al mâl) and has a positive impact on the movement of the Indonesian economy.